2017
DOI: 10.1186/s13568-017-0464-4
|View full text |Cite|
|
Sign up to set email alerts
|

Development of a circulation direct sampling and monitoring system for O2 and CO2 concentrations in the gas–liquid phases of shake-flask systems during microbial cell culture

Abstract: Monitoring the environmental factors during shake-flask culture of microorganisms can help to optimise the initial steps of bioprocess development. Herein, we developed a circulation direct monitoring and sampling system (CDMSS) that can monitor the behaviour of CO2 and O2 in the gas–liquid phases and obtain a sample without interrupting the shaking of the culture in Erlenmeyer flasks capped with breathable culture plugs. Shake-flask culturing of Escherichia coli using this set-up indicated that a high concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Liquid and gas Used RAMOS to measure in the headspace and rotating flexi-tube optical sensor to monitor dissolved O 2 , CO 2 , and culture pH Hansen, Jacob, Luchterhand, and Büchs (2012) Fluorescence-based method for monitoring CO 2 and O 2 in the culture broth and in the headspace of an Erlenmeyer flask and broth pH as well Ge and Rao (2012) Circulation direct monitoring and sampling system-a system that continuously extracts and measures liquid (by electrode) and gas-phase samples Takahashi et al (2017) Takahashi and Aoyagi (2018a, 2018b, and 2018c Abbreviations: dCO 2 , dissolved carbon dioxide; OTR, oxygen transfer rate; RAMOS, respiration activity monitoring system.…”
Section: Bluesens Gas Sensor Gmbhmentioning
confidence: 99%
See 3 more Smart Citations
“…Liquid and gas Used RAMOS to measure in the headspace and rotating flexi-tube optical sensor to monitor dissolved O 2 , CO 2 , and culture pH Hansen, Jacob, Luchterhand, and Büchs (2012) Fluorescence-based method for monitoring CO 2 and O 2 in the culture broth and in the headspace of an Erlenmeyer flask and broth pH as well Ge and Rao (2012) Circulation direct monitoring and sampling system-a system that continuously extracts and measures liquid (by electrode) and gas-phase samples Takahashi et al (2017) Takahashi and Aoyagi (2018a, 2018b, and 2018c Abbreviations: dCO 2 , dissolved carbon dioxide; OTR, oxygen transfer rate; RAMOS, respiration activity monitoring system.…”
Section: Bluesens Gas Sensor Gmbhmentioning
confidence: 99%
“…The fluorescencebased method has been reported to measure O 2 and CO 2 in the headspace as well as in culture broth. The effect of fluorescent pigment has always been debated (Ge et al, 2005;Gupta & Rao, 2003 (Takahashi & Aoyagi, 2018a, 2018bTakahashi, Sawada, & Aoyagi, 2017). However, it is critical to prevent cells from clumping to avoid the clogging of the liquid circulation part.…”
Section: Bluesens Gas Sensor Gmbhmentioning
confidence: 99%
See 2 more Smart Citations
“…Following publication of the original article (Takahashi et al 2017 ), the authors reported that there was a mistake in the legend of Figure 2, which in the published article reads as follows:…”
Section: Erratum To: Amb Expr (2017) 7:163 Doi 101186/s13568-017-046mentioning
confidence: 99%